2003
DOI: 10.1096/fj.02-1151fje
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and post‐translation regulation of the Tiel receptor by fluid shear stress changes in vascular endothelial cells

Abstract: The interaction between the vascular endothelium and hemodynamic forces (and more specifically, fluid shear stress), induced by the flow of blood, plays a major role in vascular remodeling and in new blood vessels formation via a process termed arteriogenesis. Tie1 is an orphan tyrosine kinase receptor expressed almost exclusively in endothelial cells and is required for normal vascular development and maintenance. The present study demonstrates that Tie1 expression is rapidly down-regulated in endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…Microarray analysis of HUVEC gene expression under static and 2 Pa laminar shear stress showed CLEC14A and ROBO4 were markedly upregulated (significant false discovery rate of o12% and o1% respectively) in the absence of shear stress. Real-time PCR analysis confirmed the predicted downregulation of CLEC14A and ROBO4 expression (Figure 9a) in HUVEC exposed to 2 Pa of shear stress for 24 h. TIE1 is a validated marker of reduced shear stress at the endothelial surface (Chen-Konak et al, 2003;Porrat et al, 2004;Woo et al, 2011). Double immunofluorescence staining of TIE1 and CLEC14A showed that they co-localised on tumor vessels (Figure 9b).…”
Section: Clec14a and Vascular Development In Zebrafishsupporting
confidence: 54%
“…Microarray analysis of HUVEC gene expression under static and 2 Pa laminar shear stress showed CLEC14A and ROBO4 were markedly upregulated (significant false discovery rate of o12% and o1% respectively) in the absence of shear stress. Real-time PCR analysis confirmed the predicted downregulation of CLEC14A and ROBO4 expression (Figure 9a) in HUVEC exposed to 2 Pa of shear stress for 24 h. TIE1 is a validated marker of reduced shear stress at the endothelial surface (Chen-Konak et al, 2003;Porrat et al, 2004;Woo et al, 2011). Double immunofluorescence staining of TIE1 and CLEC14A showed that they co-localised on tumor vessels (Figure 9b).…”
Section: Clec14a and Vascular Development In Zebrafishsupporting
confidence: 54%
“…Mechanosensors of shear stress in endothelial cells include integrins, G protein-coupled receptors, PECAM-1, and the membrane lipid layer (5). The most recent additions to the list of shear stress mediators are the members of the Tie family of receptor tyrosine kinases (9,10). A tyrosine kinase with immunoglobulin-like and EGF-like domains 1, Tie1 is expressed almost exclusively in endothelial cells (11).…”
Section: Introductionmentioning
confidence: 99%
“…This process is stimulated by phorbol esters as well as the physiological activators VEGF, TNFα and changes in shear stress (16,18,28,29). Constitutive and activated cleavage of Tie1 is mediated by metalloprotease activity (17).…”
Section: Resultsmentioning
confidence: 99%